Clad rolled reinforcing bars - E. S. Ovchinnikov; I. A. Ovchinnikova (Литьë и металлургия, 2020)
Premature destruction of reinforced concrete structures exposed to aggressive environmental influences is a serious problem, both from a technical and economic point of view. Carbon steel reinforcing bar embedded in concrete is usually not subject to corrosion due to the formation of a protective ion-oxide film that passivates the steel under conditions of strong alkalis in the concrete pores. However, this passivity can be disrupted by chlorides penetrating the concrete, or by carbonation reaching the surface of the reinforcing bar. Then the corrosion begins.An example of a solution to this problem is the replacement of conventional steel reinforcement with clad steel during construction. Through the closely spaced interface of two solid metals, the atoms diffuse with each other at different speeds, at a high temperature, and at a certain pressure. This creates a metallurgical bond between two solid metals, the integrity or «strength» of which depends on the «purity» of the interface between the two metals and on the atoms that make up this «transition zone» or bond.The article investigates plated rebar, to determine the possibility of production in a mill 320 OJSC «BSW – Management Company of the Holding «BMC». To study the new type of reinforcing bars, special types of research were conducted as determining the chemical composition, microstructure, and mechanical properties. The main advantages of this type of product are defined in the article.